2012
DOI: 10.1088/0953-8984/24/32/325105
|View full text |Cite
|
Sign up to set email alerts
|

On the theory of dielectric spectroscopy of protein solutions

Abstract: We present a theory of the dielectric response of solutions containing large solutes, of the nanometer size, in a molecular solvent. It combines the molecular dipole moment of the solute with the polarization of a large subensemble of solvent molecules at the solute-solvent interface. The goal of the theory is two-fold: (i) to formulate the problem of the dielectric response avoiding the reliance on the cavity-field susceptibility of dielectric theories and (ii) to separate the non-additive polarization of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
(137 reference statements)
2
18
0
Order By: Relevance
“…. Such an effect is consistent with numerical simulations and theory described by Matyushov for hydrated proteins . However, such analyses for rRNA are hampered by lack of relevant dielectric data–unlike the case for globular proteins for which numerous dielectric measurements have been reported and dipole moments checked using NMR and X‐ray databases .…”
Section: Discussionsupporting
confidence: 85%
“…. Such an effect is consistent with numerical simulations and theory described by Matyushov for hydrated proteins . However, such analyses for rRNA are hampered by lack of relevant dielectric data–unlike the case for globular proteins for which numerous dielectric measurements have been reported and dipole moments checked using NMR and X‐ray databases .…”
Section: Discussionsupporting
confidence: 85%
“…From Figure 5, we can see that nDEP of lysozyme is expected at high frequencies from 10 MHz to 10 GHz, which agrees with DEP behavior modeled in Matyushov's report [119]. In the case of myoglobin, a change of the DEP behavior is expected from nDEP to pDEP in the high frequency range between 10 MHz and 10 GHz.…”
Section: Ds Of Proteinssupporting
confidence: 86%
“…Boresch et al [10] and Matyushov [11] reported frequency dependence in simulated dielectric properties between the interaction of protein and water. The presence of protein causes the change in dielectric properties as it alters the mobility and linear conduction of a solution [6, 12].…”
Section: Introductionmentioning
confidence: 99%